EFEKTIVITAS PROGRAM DESA BERSINAR DI DESA SANGAU KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Hammed Diputra Imfyan; Khairul Amri (Cross-border, 2022)
The Desa bersih narkoba program or commonly abbreviated as the desa bersinar program is an area unit at the kelurahan or village level that has certain criteria where there are activities to prevent, eradicate, abuse and illicit drug trafficking or abbreviated as the P4GN program. The purpose of the making of this desa bersinar program is to create safe, orderly and educational conditions for rural communities against drugs so that the village environment becomes clean from drug abuse and to create villages that are independent in carrying out P4GN activities. The purpose of this study was to determine the effectiveness of the desa bersinar Program in Sangau Village, Kuantan Mudik District, Kuantan Singingi Regency. The type of research used in this research is descriptive qualitative. This research was conducted in Sangau Village and at the BNNK Kuantan Singingi Office. The required data collection is both primary and secondary data from interviews, observations, documentation, and then analyzed so that conclusions can be drawn from the research problem. The results obtained are the effectiveness of the desa bersinar program in Sangau Village, Kuantan Mudik District, Kuantan Singingi Regency has been running effectively but in the implementation of its activities it still needs to be improved. The inhibiting factor of the desa bersinar program in Sangau Village is the lack of coordination in program implementation and high community mobilization.